A successful endovascular intervention for massive hemorrhage due to a ruptured gastric artery aneurysm in a patient with microscopic polyangiitis: A case report. Issue 4 (April 2023) - Chen, Zhonghua; Zhu, Chuanfang; Zhao, Peng; Tang, Congsheng; Xiong, Yue; Yu, Yihui; Chen, Feng
Abstract: The formation of left gastric artery aneurysms (LGAAs) is a very rare complication of microscopic polyangiitis (MPA). Hemorrhage due to ruptured LGAAs is life threatening. In this case report, an 81-year-old female patient diagnosed with MPA developed massive bleeding from a ruptured LGAA and hemorrhagic shock during hospitalization. The patient underwent endovascular therapy to successfully embolize the aneurysm with microcoils and recovered postoperatively.